A processualidade da atividade gestionária na prática profissional cotidiana do assistente social: um estudo no município de Presidente Prudente – SP - Oliveira, Isabelle Almeida de (2020)
This study aims to analyze the procedurality of management activity in the dailyprofessional practice of the social worker. We consider as research support the data collection, theoretical references and the experience of social workers who work in management and / or coordination functions. We assume that management has been neglected as a technical-operative competence by social workers, although it is recognized in the documents that legislate the profession; It is also a subject that makes up the curriculum guidelines for training. In the study, we observed that social workers only recognize it in its macro dimension, in the operationalization, mainly, of public policies and not in the intrinsic process of daily practice. This is a critical qualitative research, conducted through interviews with social workers who work in management / coordination activities in various occupational partner spaces in the city of Presidente Prudente - SP